2010
DOI: 10.1044/1092-4388(2010/09-0252)
|View full text |Cite
|
Sign up to set email alerts
|

Use of Acoustic Cues by Children With Cochlear Implants

Abstract: Despite their different auditory input, children with a CI appear to be able to use many acoustic cues effectively in speech perception. Most importantly, children with a CI and normal-hearing children were observed to use similar cue-weighting patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…A substitution of [f] for /s/ is not a typical developmental sound substitution (Smit, 1993). Furthermore, previous studies have shown that /s/ is a difficult sound for individuals with CIs to identify and that /s/ is often confused with /f/ (Munson et al, 2003;Donaldson and Kreft, 2006;Giezen et al, 2010). The spectral energy of /f/ is relatively flat compared to that of /s/.…”
Section: Discussionmentioning
confidence: 87%
“…A substitution of [f] for /s/ is not a typical developmental sound substitution (Smit, 1993). Furthermore, previous studies have shown that /s/ is a difficult sound for individuals with CIs to identify and that /s/ is often confused with /f/ (Munson et al, 2003;Donaldson and Kreft, 2006;Giezen et al, 2010). The spectral energy of /f/ is relatively flat compared to that of /s/.…”
Section: Discussionmentioning
confidence: 87%
“…Implant users and normal-hearing subjects with CI simulations used formant movement and duration cues to the same extent in vowel recognition. Looking at pre-lingually deafened children who use CIs, Giezen and colleagues (2010) found that these children used similar cue-weighting strategies as children with normal hearing for three of four contrasts, /ɑ/-/a/, /ɪ/-/i/, and /bu/-/pu/. Thus, in some instances listeners using CIs rely on the same cues as listeners with normal hearing for phonemic judgments.…”
Section: Exploring Cue Weighting With Individuals With Cismentioning
confidence: 94%
“…For example, in the study by Giezen and colleagues (2010), the children with CIs used spectral cues in the /fu/-/su/ contrast less effectively than normal-hearing children. Hedrick and Carney (1997) conducted a study examining the relative contributions of formant transitions and amplitude structure to labeling decisions for synthetic fricative-vowel syllables.…”
Section: Exploring Cue Weighting With Individuals With Cismentioning
confidence: 97%
See 1 more Smart Citation
“…For example, Caldwell and Nittrouer (2013) note that CIs transmit temporal aspects of speech relatively well; consequently, voice onset time (VOT)-and by extension, stop voicingpresents an opportunity to test how well children with CIs can form phonemic categories. Giezen, Escudero, and Baker (2010) found that Dutch children with CIs differentiate stop voicing contrasts (/bu/ vs. /pu/) better than other phonemic contrasts (/fu/ vs. /su/). However, production data for stop voicing differentiation involving children with CIs are less clear in that some studies find that children with CIs produce stop VOT values within the range produced by typically developing peers (e.g., Uchanski & Geers, 2003), whereas other studies indicate that stop voicing distinctions can be acquired by children with CIs but with VOT values that are outside the typical range (Bharadwaj & Graves, 2008).…”
mentioning
confidence: 99%